Evaluasi Kinerja Karyawan di PT. KSG Pintu Teknologi Indonesia - Gandyss Adi Radia Hafsari; Sugiharto Sugiharto (Jurnal Pengabdian Masyarakat, 2025)
This proposal presents the final report of the Field Work Lecture (KKL) regarding employee performance assessment at PT. KSG Pintu Teknologi Indonesia, Surabaya branch. The objective is to identify factors that influence employee performance and provide an overview of performance improvement efforts. Observations show that the company implements a target system as a performance benchmark, which is evaluated periodically. The introduction of targets includes internal factors (motivation, work ethic, ability, welfare) and external factors (natural conditions, certain moments). The implemented solutions include a centralized information system, advanced communication/coordination, and appreciation to increase motivation. Assessor training is also emphasized to reduce bias. This report provides insights into performance management and company strategy.